A Fast and Sensitive Enzyme-Mediated Duplex Exponential Amplification Method for Field Detection of Bursaphelenchus xylophilus - Kai Guo; Xinxin Ma; Yiwu Fang; Weijun Duan; Yao Wu; Zhenxin Hu; Weimin Ye; Jianfeng Gu (Horticulturae)
The pinewood nematode (PWN), Bursaphelenchus xylophilus, is a pathogenic organism that causes pine wilt disease (PWD). To date, several molecular diagnostic methods have been developed; however, rapid, convenient, and inexpensive field diagnostic tools for detecting PWN are still limited. In this study, an enzyme-mediated duplex exponential amplification (EmDEA) method for detecting PWN from extracted nematodes or pinewood sawdust was developed and tested. This method comprised an EmDEA molecular test kit, which consisted of freeze-dried enzyme pellets that can be stored at room temperature (approximately 20–25 °C) for one year, a dry block heater, and a portable isothermal fluorescence amplification instrument. The whole procedure was completed within 30 min. The EmDEA assay could detect a single PWN at all life stages from a mixture of other nematode species or from pinewood sawdust. The detection limit was 10 copies (plasmid weight 32.66 ag) or 1/500 of that of a single adult PWN per reaction. Therefore, the EmDEA assay has potential applications in PWN detection in the field, as well as quarantine inspection in international trade. Moreover, modification of primers and probes will allow the rapid identification of other nematode species.